2022
DOI: 10.1007/s00421-022-04946-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrate supplementation on skeletal muscle motor unit activity during isometric blood flow restriction exercise

Abstract: Background Nitrate (NO3−) supplementation has been reported to lower motor unit (MU) firing rate (MUFR) during dynamic resistance exercise; however, its impact on MU activity during isometric and ischemic exercise is unknown. Purpose To assess the effect of NO3− supplementation on knee extensor MU activities during brief isometric contractions and a 3 min sustained contraction with blood flow restriction (BFR). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…Wylie et al [ 9 ] have previously attributed enhanced performance in the Yo–Yo IR1 test to attenuated muscle excitability due to a net loss of potassium. Further, it has been reported that NO 3 − supplementation attenuated the increase in motor unit action potential (MUP) duration [ 42 ]. Shorter MUP duration may result in a faster muscle fiber conduction velocity and greater sarcoplasmic reticulum calcium release and thus maintained force production in the face of fatigue development [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wylie et al [ 9 ] have previously attributed enhanced performance in the Yo–Yo IR1 test to attenuated muscle excitability due to a net loss of potassium. Further, it has been reported that NO 3 − supplementation attenuated the increase in motor unit action potential (MUP) duration [ 42 ]. Shorter MUP duration may result in a faster muscle fiber conduction velocity and greater sarcoplasmic reticulum calcium release and thus maintained force production in the face of fatigue development [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…potential (MUP) duration [42]. Shorter MUP duration may result in a faster muscle fiber conduction velocity and greater sarcoplasmic reticulum calcium release and thus maintained force production in the face of fatigue development [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Then, maximum voluntary contractions (MVCs) of the knee extensors were performed by using a custom-built dynamometer [32] to determine individual 25% MVC for submaximal exercise protocol. The exercise protocol has been described elsewhere in detailed [33]. Briefly, a 20 s contraction at 25% MVC was performed firstly; then, a blood flow occlusion (BFO) period was applied at the proximal thigh (with 220 mmHg) for 8 min, with a sustained submaximal contraction at 25% MVC in the final 3 min of the BFO period.…”
Section: Methodsmentioning
confidence: 99%
“…As such, the reduction of CMC during the initial phase of contraction is unlikely to be explained solely by the presence of elevated experimental pain. It is therefore possible that CMC was primarily modulated by altered activation (via cuff compression) and sensitivity (via metabolite accumulation) of mechanoreceptors (Zambolin et al, 2022(Zambolin et al, , 2023 which would have impaired the feedback/feed-forward mechanism required to finely regulate muscle tension and motor unit recruitment in a manner that supports isometric force precision during the early phase of contraction. Additionally, Ushiyama et al (2011) found that CMC was actually enhanced during isometric contractions of the tibialis anterior when preceded by a fatiguing task, despite increased EMG activity, increased RPE, and poorer force steadiness.…”
Section: Occlusion Of the Exercising Leg (Ips-occ)mentioning
confidence: 99%
“…We also did not measure exhaustive exercise or implement neuromuscular assessments to discern between central and/or peripheral fatigue (Gandevia, 2001). Implementing measures for detecting changes in motor unit recruitment and firing rate (i.e., via intramuscular or high‐density EMG) could be useful strategies to address this short‐coming and overcome the limitations of bipolar surface EMG (Esen et al., 2022; Vieira & Botter, 2021). It should also be highlighted that we observed no significant changes in cortical beta activity between our experimental conditions.…”
Section: Study Limitationsmentioning
confidence: 99%